Photodynamic Therapy in Primary Breast Cancer - Banerjee, Shramana M. (J Clin Med, 2020)
Photodynamic therapy (PDT) is a technique for producing localized necrosis with light after prior administration of a photosensitizing agent. This study investigates the nature, safety, and efficacy of PDT for image-guided treatment of primary breast cancer. We performed a phase I/IIa dose escalation study in 12 female patients with a new diagnosis of invasive ductal breast cancer and scheduled to undergo mastectomy as a first treatment. The photosensitizer verteporfin (0.4 mg/kg) was administered intravenously followed by exposure to escalating light doses (20, 30, 40, 50 J; 3 patients per dose) delivered via a laser fiber positioned interstitially under ultrasound guidance. MRI (magnetic resonance imaging) scans were performed prior to and 4 days after PDT. Histological examination of the excised tissue was performed. PDT was well tolerated, with no adverse events. PDT effects were detected by MRI in 7 patients and histology in 8 patients, increasing in extent with the delivered light dose, with good correlation between the 2 modalities. Histologically, there were distinctive features of PDT necrosis, in contrast to spontaneous necrosis. Apoptosis was detected in adjacent normal tissue. Median follow-up of 50 months revealed no adverse effects and outcomes no worse than a comparable control population. This study confirms a potential role for PDT in the management of early breast cancer.